Culture orientation and deception in Singapore. - Ng, Siew Mein. (2008)
Individualism and collectivism has been the focus of tremendous research interest in cross-cultural psychology since the 1980s. However, studies have yet to present evidence concerning cultural differences in the tendency to deceive. Thus, it has inspired us to carry out this research between culture and deception in the local context.